Peran Herpetofauna dalam Bidang Kesehatan: Peluang dan Tantangan - Aditya K. Karim; Zainal A. Wasaraka; Linus Y. Chrystomo; Ervina Indrayani (Jurusan Biologi FMIPA Universitas Cenderawasih, 2012)
Skin secretions and venom from many species of amphibi (frogs and toads) and reptil (group of herpetofauna) from different famillies contain a wide range of unique physiological compounds with biological activity such as peptide, protein, non-protein, and enzyme. They are potent for drug development. The compounds, known as mode of action have practical application as pharmaceutical agents, diagnostic reagents or preparative tools. Peptides with potential anticancer, fibrinolityc, antibacterial, antifungal, antidiabetic activity play important roles in human health. This review introduces roles of herpetofauna for drugs development, potential therapeutic values and their application in human health and disease.Key words: Herpetofauna, skin secretion, venom, drugs development, health.